M.A.S.H : when television changed forever [videorecording (DVD)] - Weinthal, Eric; Gauchat, Sara; Farr, Jamie, 1934-; Farrell, Mike; Maxwell, Jeff, 1947- (AMS Pictures, 2025)
MASH: When Television Changed Forever is the definitive 50th anniversary celebration of one of the most enduring and important television series in history. Featuring exclusive interviews with cast members, series producers, and writers, the documentary reflects on the incredible risks MASH took to become the most-watched scripted show of all time.